Gorky and Moscow art theatre: selective affinities - Marie-Christine Autant-Mathieu (Studia Litterarum)
Gorky started his literary career as a playwright at the Moscow Art Theatre. He wrote his first plays for its troupe in competition with Chekhov whose plays were performed there during the same period. Thus, two Moscow Art Theatre directors, Stanislavsky and Nemirovich-Danchenko dealts with two authors whom they valued but whose approaches differed. My paper that forms part of a study concerning Gorky’s collaboration with the Moscow Art Theatre, focuses on the way in which Stanislavsky and Nemirovich-Danchenko revised and embellished the history of their relationship with Gorky in their autobiographies both written in the Soviet period, My Life in Art (1926) and My Life in the Russian theatre (1936) respectively. In real fact, the relationship was problematic due to Gorky’s political opinions and the difficulties that the actors encountered playing his characters. Since the middle of the 1920s, Gorky became a defender of the Moscow Art Theatre and consequently, the two directors put their political and aesthetic contradictions aside and sought to reconcile themselves with Gorky who contributed to make the Art Moscow Theatre a model Soviet theatre. Besides, the writer supported Stanislavsky in founding an opera-dramatic studio in 1935 and writing and publishing “The Stanislavsky System.”